Chemical profiles and antimicrobial activities of Thai propolis collected from Apis mellifera - Sirikarn Sanpa (2018)
© 2017, Chiang Mai University. All rights reserved. The aim of this study was to examine the antimicrobial properties and chemical composition of Thai Apis mellifera propolis from different locations. All propolis samples demonstrated significant activity (Minimal Inhibitory Concentration < 1000 µg/mL) against Gram-positive bacteria Bacillus cereus, Staphylococcus aureus, S. epidermidis and methicillin-resistant Staphylococcus aureus (MRSA) whereas the activities against Gram-negative bacteria and yeasts were lower. There were statistically significant differences (p < 0.001) between the Thai propolis extracts due to their DPPH free radical scavenging activity and total phenolic contents. The GC/MS chemical profiles of all the propolis samples demonstrated similar composition but different proportion of sugars and sugar derivatives, triterpenes and phenolic lipids. From the most active sample (Phayao), several triterpenes and three inseparable mixtures of phenolic lipids (cardols, cardanols, and anacardic acids) were isolated by chromatographic methods and they showed high antibacterial activities. This indicates that propolis from the studied regions belongs to the tropical propolis type, originating mainly from mango (Mangifera indica). Our results provide the information that is useful for future standardization of Thai propolis.